Theodicy and hope in the Book of the Twelve - Athas, George ca. 20./21. Jh.; Stovell, Beth M. 1978-; Timmer, Daniel C.; Toffelmire, Colin M. (London Bloomsbury Publishing Plc, 2021)
Cover -- Titel -- Copyright -- Contents -- List of Contributors -- Abbreviations -- Introduction / Beth M. Stovell and Daniel C. Timmer -- Chapter 1 Theodicy and Hope in the Book of the Twelve / Grace Ko -- Chapter 2 Exile and Re-exile in the Book of the Twelve / Anthony R. Petterson -- Chapter 3 "How Can I Give You Up, Ephraim?" (Hosea 11:8a): Theodicy in Hosea / Brittany Kim -- Chapter 4 Hope through Human Trafficking? Theodicy in Joel 4:4-8 / Heath A. Thomas -- Chapter 5 The Lawlessness of the Lion-God: Theodicy in the Book of Amos / Chelsea D. Mak -- Chapter 6 Theodicy in Micah / Rainer Kessler -- Chapter 7 "Ah, Assyria Is No More!" Retribution, Theodicy, and Hope in Nahum / Daniel C. Timmer -- Chapter 8 The Triumph of Hope in Habakkuk / David J. Fuller -- Chapter 9 The Hope of Habakkuk in the Anthropocene Age / Michael H. Floyd -- Chapter 10 Creating and Bridging the Gap: Assyria and Babylon in the Presentation of Theodicy and Hope in the Book of the Twelve / Mark J. Boda -- Chapter 11 The Failure of Davidic Hope? Configuring Theodicy in the Book of the Twelve in Support of a Davidic Kingdom / George Athas -- Bibliography -- Index of References -- Index of Authors.
Description based on publisher supplied metadata and other sources
Keywords: Theodicy-Biblical teaching; Electronic books; Aufsatzsammlung